Pengaruh Literasi Digital dan Sertifikasi Kompetensi terhadap Employability Mahasiswa melalui Kompetensi Kerja sebagai Variabel Mediasi - Diksi Metris; Ahmad Daffa Prayoga; Ananda Rinjani Faatihah; Rajendra Gading Pramudya; Sapto Dwi Mulyana (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2026)
This study aims to analyze the influence of digital literacy and competency certification on student employability, with work competency as a mediating variable. The background of this research stems from the still high Open Unemployment Rate (OUR) among university graduates. Data from the Central Bureau of Statistics (BPS) show that in August 2025, the unemployment rate in Indonesia will still reach 4.85 percent, indicating a gap between graduates' competencies and the needs of the workforce in the digital era. This condition confirms that students' employability is no longer solely determined by their academic degrees, but also by their digital literacy skills, possession of competency certifications, and mastery of practical work competencies. This research uses a quantitative approach with a survey method for students, and the data is analyzed using path analysis or Structural Equation Modeling (SEM) to test both direct and indirect effects between variables. The research results indicate that digital literacy and competency certification have a positive and significant impact on student employability. Both variables were also proven to have a significant impact on work competence. The main findings of this study confirm that work competence has the strongest influence on employability and acts as a mediating variable that strengthens the influence of digital literacy and competence certification. Thus, the improvement of students' employability is highly dependent on the successful internalization of digital skills and competency certification into work competencies relevant to the demands of the working world. This research provides theoretical and practical implications for universities in designing curricula and learning strategies that are oriented toward strengthening work competencies and preparing graduates to enter the job market.